Anti-sortilin1 Antibody Up-Regulates Progranulin via Sortilin1 Down-Regulation - Miyakawa, Shuuichi; Sakuma, Hiroyuki; Warude, Dnyaneshwar; Asanuma, Satomi; Arimura, Naoto; Yoshihara, Tomoki; Tavares, Daniel; Hata, Akito; Ida, Koh; Hori, Yuri; Okuzono, Yuumi; Yamamoto, Syunsuke; et al. (Frontiers in Neuroscience, 2020)
Progranulin (PGRN) haploinsufficiency associated with loss-of-function mutations in the granulin gene causes frontotemporal dementia. This suggests that increasing PGRN levels could have promising therapeutic implications for patients carrying GRN mutations. In this study, we explored the therapeutic potential of sortilin1 (SORT1), a clearance receptor of PGRN, by generating and characterizing monoclonal antibodies against SORT1. Anti-SORT1 monoclonal antibodies were generated by immunizing Sort1 knockout mice with SORT1 protein. The antibodies were classified into 7 epitope bins based on their competitive binding to the SORT1 protein and further defined by epitope bin-dependent characteristics, including SORT1-PGRN blocking, SORT1 down-regulation, and binding to human and mouse SORT1. We identified a positive correlation between PGRN up-regulation and SORT1 down-regulation. Furthermore, we also characterized K1-67 antibodies via SORT1 down-regulation and binding to mouse SORT1 in vivo and confirmed that K1-67 significantly up-regulated PGRN levels in plasma and brain interstitial fluid of mice. These data indicate that SORT1 down-regulation is a key mechanism in increasing PGRN levels via anti-SORT1 antibodies and suggest that SORT1 is a potential target to correct PGRN reduction, such as that in patients with frontotemporal dementia caused by GRN mutation.